Staging of Early-Stage Lung Cancer without Routine PET in Candidates for Segmentectomy - Lopez-Pastorini, Alberto; Tatli, Zehra; von Bargen, Antonia; Faltenberg, Dennis; Beling, Hendrik; Koryllos, Aris; Galetin, Thomas; Stoelben, Erich (The Thoracic and Cardiovascular Surgeon, 2024)
Introduction We aimed to investigate the accuracy of clinical staging without the routine use of positron emission tomography/computed tomography (PET/CT) in patients with cIA1 and cIA2 non-small-cell lung cancer (NSCLC) scheduled for segmentectomy.Methods A total of 305 consecutive segmentectomies were retrospectively analyzed. Overall survival was calculated using the Kaplan–Meier method. Logistic regression was performed to investigate factors independently associated with pathologic upstaging.Results The Union for International Cancer Control (UICC) upstaging was found in 86 patients (28%). Upstaged patients had longer operative times (146 ± 46 vs. 131 ± 44 minutes, p = 0.009), a higher number of lymph node resection (17 ± 10 vs. 13 ± 8, p = 0.001), and a higher rate of L1 involvement (34 vs. 16%, p < 0.001) than nonupstaged patients. N1 was found in 10 patients (3%) and N2 in 13 patients (4%). Nodal positive patients had longer operation times (154 ± 50 vs. 133 ± 44 minutes, p = 0.031) and higher rates of R1 (9 vs. 1%, p = 0.006) and L1 (39 vs. 20%, p < 0.026) than patients without nodal involvement. The 3- and 5-year overall survival rates for nonupstaged and upstaged patients were 85 and 67% and 67 and 54%, respectively (p = 0.040). In logistic regression, L1 involvement (odds ratio [OR]: 2.394, p = 0.005) and the number of dissected lymph nodes (OR: 1.037, p = 0.016) were independently associated with upstaging. Patients who received PET as part of clinical staging did not have a significantly lower nodal upstaging.Conclusion Selective use of PET/CT based on the results of CT may be a viable option for patients with proven or suspected NSCLC up to 2 cm in size.
Keywords: lung cancer; lung cancer treatment (surgery medical); positron emission tomography; thoracoscopy/VATS